553 NEURODEVELOPMENTAL OUTCOMES OF PRETERM SMALL FOR GESTATIONAL AGE INFANTS BORN TO MOTHERS WITH AND WITHOUT PREECLAMPSIA. (1st January 2006) - Rogers, E. E.; Leonard, C.; Piecuch, R.
Abstract : Objective: Previous studies have investigated links between adverse neurodevelopmental outcomes and preterm small for gestational age (SGA) infants. Of the many causes of SGA infants, placental insufficiency caused by maternal hypertension or preeclampsia is well described and accounts for a significant portion of the preterm SGA infant population. We evaluated the neurodevelopmental outcomes of preterm infants born SGA dependent on whether the mother was known to have preeclampsia versus other causes of being SGA. Methods: Using the UCSF Intensive Care Nursery Follow-Up Program database, we evaluated infants treated at UCSF who were both preterm (24-35 weeks GA) and SGA (growth parameters on two premature infant growth standards < 10th percentile) between 1999 and 2004. Infants were followed after discharge in the Follow-Up Program and were evaluated with measurement of growth parameters, neurologic exam by nurse practitioner and/or physician, and either Bayley or WPPSI developmental assessment. We then compared outcomes of infants whose mothers were known to have preeclampsia as diagnosed by our maternal fetal medicine service with those without preeclampsia. Results: Our sample included a total of 72 preterm SGA infants. Of these, 54 have been evaluated in follow-up. Of the 54, 28 were born to mothers with known preeclampsia and 25 to mothers without preeclampsia. The difference in the mean birth weight, gestational age, and incidence of symmetric vs asymmetric growth of each group was not significant. The cohort with preeclampsia had no definite diagnosis of neurologic or developmental delay or disability, whereas the cohort without preeclampsia had three abnormal neurologic or developmental diagnoses. Head circumference was below the 10th percentile on follow-up for 17% of infants born to mothers with preeclampsia and 37% of infants born to mothers without preeclampsia, and abnormal head circumference was associated with adverse neurodevelopmental outcome, with 18% (2/11) showing abnormality vs 2.5% (1/40) of infants with normal head circumference. Conclusion: Preterm SGA infants born to mothers with preeclampsia have improved neurodevelopmental outcomes when compared to their preterm counterparts who are SGA due to other factors, regardless of initial symmetric or asymmetric growth at birth. Further investigation is warranted to further delineate relationship between catch-up head growth and outcomes which would allow the close observation of head circumference as a marker for neurodevelopment.